Elaboração do plano de manutenção de uma refinaria de sal da cidade de Mossoró/RN - Néo, Lídia Carolina de Moura (Universidade Federal Rural do Semi-Árido, 2018)
This work presents a study on the maintenance area of a salt refinery located in the city of Mossoró / RN. The process of producing refined salt is increasingly demanding and evolved. And the control of flaws and defects comes into this medium as an essential concept. Due to the automation of the processes and consequently the use of machinery, an efficient maintenance plan is necessary, considering the severe way the salt acts under the equipment used. The execution of procedures to prevent failures becomes essential to ensure the proper functioning of equipment and to reduce downtime. The main objective of this work is to prepare a maintenance plan in a salt refinery located in the city of Mossoró. With this, it was analyzed how maintenance is performed in the company and from there a plan was elaborated to supply the needs of the organization. For this purpose, a bibliographical study was carried out on the related subjects, as well as a case study within the company, through visits to the refinery, interviews with the employees and data collection necessary for analysis. The plan was developed according to the specifications of NBR 5462 (ABNT 1994), several documents pertinent to the plan were worked out as a work order and preventive maintenance plan. With its implementation of the plan, it is expected that the company will be able to reduce its costs with corrective maintenance and reduce downtime with equipment that is defective.
Monografia
Keywords: Manutenção; Sal; Refinaria; Plano de manutenção.; Maintenance; Salt; Refinery; Maintenance plan; ENGENHARIAS::ENGENHARIA DE PRODUCAO